2018
DOI: 10.1039/c7sc05334g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dyes and probes for super-resolution microscopy of microtubules and tracheoles in living cells and tissues

Abstract: Nanoscopy compatible fluorescent tubulin probes can be used to stain microtubules and chitin-rich taenidia in the insect tracheoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 48 publications
2
86
0
Order By: Relevance
“…We have previously demonstrated that the performance of the tubulin probes depends on the chosen taxane ligand, and that the optimal ligand is different for each fluorophore 8 . Based on thisknowledge, we synthesized a new series of tubulin probes by coupling the 4’-regioisomers of TMR-COOH and 580CP-COOH fluorophores to a Larotaxel derivative ( LTX-C8-NH 2 , ( SI-4 )) and 610CP-COOH and SiR-COOH to a Cabazitaxel derivative ( CTX-C8-NH 2 , ( SI-3 )) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that the performance of the tubulin probes depends on the chosen taxane ligand, and that the optimal ligand is different for each fluorophore 8 . Based on thisknowledge, we synthesized a new series of tubulin probes by coupling the 4’-regioisomers of TMR-COOH and 580CP-COOH fluorophores to a Larotaxel derivative ( LTX-C8-NH 2 , ( SI-4 )) and 610CP-COOH and SiR-COOH to a Cabazitaxel derivative ( CTX-C8-NH 2 , ( SI-3 )) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rhodamine probes are prone to aggregation, which significantly contributes to their fluorogenicity and might impair interaction with the target 8 . We observed a high correlation between fluorescence increase after binding to tubulin and after SDS addition, which indicates that affinity towards tubulin is sufficient to dissociate the probe from the aggregates (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations